2020
DOI: 10.1021/acsanm.0c02300
|View full text |Cite
|
Sign up to set email alerts
|

High Axial and Lateral Resolutions on Self-Assembled Gold Nanoparticle Metasurfaces for Live-Cell Imaging

Abstract: A plasmonic metasurface composed of homogeneously self-assembled gold nanoparticles can provide high-contrast fluorescence images confined to the nanointerface. In this study, we successfully demonstrated real-time, high-spatiotemporal-resolution imaging of adhered Venus-paxillin-3T3 live cells under a widefield microscope, where not only a high axial resolution but also a high lateral resolution down to the theoretical limit were confirmed through nascent cluster formation of paxillin. The improved lateral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The plasmonic metasurface-mediated imaging allows for live-cell imaging with high spatial resolutions even during cell movement due to the properties of the metasurface, which has an extremely high refractive index and acts as a nanothickness plane light emitter. [33] We also found that the plasmonic metasurface minimizes photobleaching owing to the increase in the emission efficiency via plasmon-exciton coupling, which is an important advantage for maintaining high contrast and resolution in long-term live-cell imaging. [33] Previous studies observed matured FAs of well spread cells after overnight incubation in order to establish the methodology for live-cell imaging using our plasmonic metasurface.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…The plasmonic metasurface-mediated imaging allows for live-cell imaging with high spatial resolutions even during cell movement due to the properties of the metasurface, which has an extremely high refractive index and acts as a nanothickness plane light emitter. [33] We also found that the plasmonic metasurface minimizes photobleaching owing to the increase in the emission efficiency via plasmon-exciton coupling, which is an important advantage for maintaining high contrast and resolution in long-term live-cell imaging. [33] Previous studies observed matured FAs of well spread cells after overnight incubation in order to establish the methodology for live-cell imaging using our plasmonic metasurface.…”
Section: Introductionmentioning
confidence: 68%
“…[33] We also found that the plasmonic metasurface minimizes photobleaching owing to the increase in the emission efficiency via plasmon-exciton coupling, which is an important advantage for maintaining high contrast and resolution in long-term live-cell imaging. [33] Previous studies observed matured FAs of well spread cells after overnight incubation in order to establish the methodology for live-cell imaging using our plasmonic metasurface. Taking advantages of our plasmonic metasurface-mediated imaging technique such as high spatial resolution and minimal photobleaching, we apply our imaging technique to observe initial cell adhesion behavior where cells start to adhere through weak and unstable interactions susceptible for photobleaching.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations